2010
DOI: 10.1073/pnas.1002642107
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of resting and ligand-bound ErbB1 and ErbB2 receptor tyrosine kinases in living cells using number and brightness analysis

Abstract: Ligand-driven dimerizations of ErbB receptor subunits fulfill a fundamental role in their activation. We have used the number and brightness analysis technique to investigate the existence of preformed ligand-independent dimers and clusters and to characterize the initial steps in the activation of ErbB1 and ErbB2. In cells expressing 50,000-200,000 receptors, ErbB1 was monomeric in the absence of ligand stimulation, whereas in CHO cells with receptor levels >500,000 as much as 30% of ErbB1 was present as pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
161
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 58 publications
13
161
3
Order By: Relevance
“…1E-G). Ligand-independent signaling has been reported for overexpression of Egfr in Drosophila and in mammalian cells, where the high levels of Egfr are thought to cause spontaneous dimerization and signaling (Schweitzer et al, 1995;Nagy et al, 2010;Endres et al, 2013). Our results suggest that, at the normal physiological level of the receptor in the fly embryo, all signaling is ligand dependent.…”
Section: Resultssupporting
confidence: 54%
“…1E-G). Ligand-independent signaling has been reported for overexpression of Egfr in Drosophila and in mammalian cells, where the high levels of Egfr are thought to cause spontaneous dimerization and signaling (Schweitzer et al, 1995;Nagy et al, 2010;Endres et al, 2013). Our results suggest that, at the normal physiological level of the receptor in the fly embryo, all signaling is ligand dependent.…”
Section: Resultssupporting
confidence: 54%
“…We found that phosphorylated forms of HER2 and EGFR were present in MCF-7-derived exosomes (Fig. 4A), possibly due to the ligand-independent dimerization and activation of EGFR family members (44,45). To exclude the artificial effect of the total exosome isolation reagent on RTK activation, we also examined the expression of phosphorylated EGFR and HER2 in MCF-7-derived exosomes that were isolated using both a traditional ultracentrifugation method and the isolation kit from Invitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ErbB1 expressed at levels of 50,000 -200,000 receptors per cell is monomeric. At receptor numbers greater than 500,000, ϳ30% of these receptors are in preformed dimers (58). Moreover, lateral compartmentalization can only increase the likelihood of apparent FRET.…”
Section: Discussionmentioning
confidence: 99%